العلاقة بين مفهوم الذات ومهارة الكلام لدى طالبات الصف الأول في المرحلة الثانوية بمعهد الإمام مسلم ساي رمباه: The Relationship of Self-Concept Profile and Speaking Skill Proficiency on the First-Grade Female Student in Secondary School at Imam Muslim Sei Rampah - Anisa Maulidya (El-Jaudah : Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
Abstract: This study aims to know the self-concept profile and speaking skill proficiency and a relationship between both of them on the first-grade female students in secondary school at Imam Muslim Sei Rampah. The research methodology used is a quantitative correlational method using statistical data with the Spearman rank formula to obtain the research results. The result of this research is known the level of self-concept among the first-grade female students in secondary school at Imam Muslim Sei Rampah is classified as good, with a percentage of 43%, which means 13 students. The level of speaking skill proficiency among first-grade female students in secondary school at Imam Muslim Sei Rampah is classified as good, with a percentage of 50%, which means 15 students. There is a significant positive relationship between self-concept and speaking skill proficiency among the first-grade female students in secondary school at Imam Muslim Sei Rampah, with a correlation coefficient of 0.693, representing 69%, indicating a moderate and positive correlation. Key words: Self-Concept, Speaking Skill, Arabic Speaking Skills. مستخلص البحث: يهدف هذا البحث لمعرفة صورة مفهوم الذات وقدرة على مهارة الكلام وعلاقة بينهما لدى طالبات الصف الأول في المرحلة الثانوية بمعهد الإمام مسلم ساي رمباه. استخدمت الباحثة المنهج المنهج الكمي بالنوع العلاقي مع طريقة تحليل البيانات الإحصائية بالرمز علاقة (spearman rank) . ونتيجة البحث تدل على أن مفهوم الذات لطالبات الصف الأول في المرحلة الثانوية بمعهد الإمام مسلم ساي رمباه في صنف جيد بالنسبة 43% يعني 13 طالبة، وقدرة مهارة الكلام لديهم في صنف جيد بالنسبة 50% يعني 15 طالبة، وعلاقة بين مفهوم الذات ومهارة الكلام بقيمة معامل الارتباط 0,693 بالنسبة 69% والعلاقة معتدلة باتجاه إيجابي. الكلمات الأساسية : مفهوم الذات، مهارة الكلام، مهارة الكلام باللغة العربية.